(untitled) (University Journal of Zoology, Rajshahi University, 2012)
Fecundity and egg viability of Tribolium castaneum (Herbst) females were significantly (P<0.01) reduced by synthetic pyrethroids and an alkaloid containing insecticide nimbicidine. In control, the average number of eggs laid by each female/day was 12.18. The lowest number of eggs laid by each female/day was noted as 4.38 when combining nimbicidine with two pyrethroids i.e., cypermethrin and deltamethrin. The percentage of egg hatching without insecticide treatment was 95%. The lowest percent of egg hatching was 63.95 when the adult female was fed on flour medium treated with combined doses of cypermethrin, deltamethrin and nimbicidine. Among the treated insecticides, nimbicidine (80.69%) proved effective in reducing the fertility than those of cypermethrin (86.05%) and deltamethrin (88.52%). Key words: Tribolium; cypermethrin; deltamethrin; nimbicidine; fecundity; fertility DOI: http://dx.doi.org/10.3329/ujzru.v29i1.9461 UJZRU 2010; 29(1): 23-27